Grain boundary wetting correlated to the grain boundary properties: A laboratory-based multimodal X-ray tomography investigation. (1st April 2019) - Sun, J.; Zhang, Y.; Lyckegaard, A.; Bachmann, F.; Lauridsen, E.M.; Juul Jensen, D.
Abstract: The penetration behavior of liquid gallium in aluminum is characterized using laboratory X-ray attenuation tomography and related to grain boundary properties obtained from the 3D grain map reconstructed by laboratory diffraction contrast tomography (LabDCT). The data is unique because more than 100 grain boundaries are analyzed. It is suggested that it is the grain boundary energy which determines if a boundary is wetted or not: low energy boundaries are much more resistant to liquid gallium than higher energy ones. The potentials of using laboratory diffraction contract tomography for statistical studies of grain boundaries are thereby demonstrated. Graphical abstract: Grain boundary wetting phenomenon is investigated using laboratory multimodal X-ray imaging techniques that combines attenuation contrast tomography and diffraction contrast tomography. A large statistic of grain boundaries reveals the correlation between the preferential penetration path of liquid Ga in Al matrix and the properties of grain boundaries.Unlabelled Image